Analisis Faktor Penyebab Perilaku Seksual Pranikah pada Remaja di Desa Wedomartani Sleman Yogyakarta - Suwarsi Suwarsi (Alma Ata University Press, 2016)
The results of a preliminary study that was conducted on October 3, 2014 in the working area through community leaders that the data obtained in the region ﬁnd teenagers who use modern mobile phone is already making it easier for adolescents to access information related to sexual behavior. In 2014 there was one case of students expelled because of unwanted pregnancies. The purpose of study was to determine the factors that causing the premarital sexual behavior in adolescents in Wedomartani village, Sleman. Study methods used was quantitative with analytical research using chi-square test, with a sample of 80 adolescents. The results showed that characteristics of teens in the village of Sleman Wedomartani ever be free of sexual behavior lifespan of 12 years to 26 years, with the majority age of 20 years (25%). Characteristics of free sex through exposure on TV media majority are at no risk category (55%), whereas the risk of exposure to teenage promiscuity through TV media as much as 45%. Characteristics of adolescents ever accessing pornography through the Internet as much as 45 teenagers or 56.3%. In conclusions, there was signiﬁ cant relationship between TV exposure and accessing pornography on the Internet toward adolescents premarital sexual behavior in the Wedomartani village of Sleman.